2020
DOI: 10.21203/rs.3.rs-130640/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epicardial adipose tissue volume and coronary calcification among people living with diabetes: a cross-sectional study

Abstract: Background Epicardial adipose tissue (EAT) has anatomic and functional proximity to the heart and is considered a novel diagnostic marker and therapeutic target in cardiometabolic diseases. The aim of this study was to evaluate whether EAT volume was associated with coronary artery calcification (CAC) in people living with diabetes, independently of confounding factors.Methods We included all consecutive patients with diabetes whose EAT volume and CAC score were measured using computed tomography between Janua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…As our correlation analyses showed, age and EAT were both independent factors that inversely correlated with LV-GLS and LA strains. Several previous studies also found a strong relation between age and EAT (14,33). In the study by de Vos et al age-adjusted regression analyses showed that EAT was positively related to weight, BMI, waist circumference, waist-to-hip ratio and subclinical coronary atherosclerosis (34).…”
Section: Potential Mechanisms Underlying the Influence Of Epicardial ...mentioning
confidence: 84%
“…As our correlation analyses showed, age and EAT were both independent factors that inversely correlated with LV-GLS and LA strains. Several previous studies also found a strong relation between age and EAT (14,33). In the study by de Vos et al age-adjusted regression analyses showed that EAT was positively related to weight, BMI, waist circumference, waist-to-hip ratio and subclinical coronary atherosclerosis (34).…”
Section: Potential Mechanisms Underlying the Influence Of Epicardial ...mentioning
confidence: 84%
“…Risk factors for CAD are classified according to the following criteria: (A) Hypertension: systolic blood pressure > 140 mmHg and/or diastolic blood pressure > 90 mmHg and/or use of antihypertensive medication according to the guidelines [29]; (B) Dyslipidaemia: dyslipidaemia defined as fasting total cholesterol > 6.2 mmol/L, low-density lipoprotein (LDL) cholesterol > 3.4 mmol/L, high-density lipoprotein (HDL) cholesterol < 1.0 mmol/L, serum triglycerides > 1.7 mmol/L (outpatient only), or diagnosis/ treatment of dyslipidaemia [30]; (C) Diabetes mellitus: patients on oral hypoglycaemic agents or insulin or with fasting blood glucose ≥ 7.0 mmol/L are defined as T2DM [31]; (D) Family history of CAD: family history of ≥ 1 degree of consanguinity with CAD before age 60 [20]; (E) Obesity: BMI ≥ 28 kg/m 2 is considered to be obese [32]. Diabetes-related complications include (A) retinopathy: any medical basis for retinopathy; (B) neuropathy: any sign or symptom of polyneuropathy; (C) peripheral arterial occlusive disease: 50% stenosis on ultrasonography; and (D) nephropathy: renal failure, i.e., glomerular filtration rate < 60 mL/min and/or micro or macro proteinuria [33,34].…”
Section: Data Collectionmentioning
confidence: 99%
“…This is surprising, as we recently reported an independent association between EAT volume measured with CT and CAC score in 409 patients with diabetes. 9 This may be atributable to insufficient statistical power, as this subanalysis was not prespecified in the original study 2 and no sample size calculation could be performed beforehand.…”
mentioning
confidence: 99%